VD_FINDINFO Décision / 2017 / 417 vom 7. Juni 2017 - VD Tribunal cantonal (2017)
DÉTENTION POUR DES MOTIFS DE SÛRETÉ, DROIT D'ÊTRE ENTENDU, PROPORTIONNALITÉ | 29 Cst., 231 al. 1 CPP (CH), 237 CPP (CH), 393 al. 1 let. b CPP (CH)